Single nucleotide polymorphism of prostaglandin-endoperoxide Synthase (PTGS2) and defensin Beta 1 (DEFB1) genes in Malay chronic periodontitis subjects / Jasmin Kaur Jagender Singh - Jasmin Kaur, Jagender Singh (2020)
The association of prostaglandin-endoperoxide synthase 2 (PTGS2) and defensin beta 1 (DEFB1) single nucleotide polymorphisms (SNP) with chronic periodontitis (CP) have been widely studied amongst different ethnic groups such as the Chinese and European population. Thus far, no study has been done on the Malay ethnic group. Hence, this study assessed the allele and genotype frequencies of PTGS2 and DEFB1 variants in subjects with CP and periodontally healthy individuals in Malaysian Malays. Samples of 78 Malay CP subjects and 62 periodontally healthy controls were obtained from Malaysian Periodontal Database and Biobanking system (MPDBS) for this study. DNA samples were genotyped for 3 candidate SNPs from PTGS2 (rs5275, rs20417, rs689466) and 1 from DEFB1 (rs1047031) using TaqMan SNP genotyping assays. The rs20417 and rs689466 are SNPs in the promoter region while rs5275 and rs1047031 are located in the 3′ untranslated region of the transcript. The allelic and genotypic associations between the SNPs and CP were investigated. We did not find any significant associations between these SNPs and CP risk (p>0.05) in the Malay ethnic group. No association was found in this study and this might be due to the small sample size and hence further study using larger sample size is required to confirm our findings. Keywords: PTGS2, DEFB1, cytokines, Defensin, single nucleotide polymorphism, chronic periodontitis, allele, gene, genotyping